HIV/AIDS in the South-East Asia region: progress and challenges - Razia Pendse; Somya Gupta; Dongbao Yu; Swarup Sarkar (Elsevier, 2016)
The South-East Asia region, with 11 member states, has an estimated 35 million people living with HIV (PLHIV) More than 99% of PLHIV live in five countries where HIV prevalence among the population aged 15-49 remains low but is between 2% and 29% among key populations Since 2010, the region has made progress to combat the epidemic Mature condom programmes exist in most countries but opioid substitution therapy, and needle and syringe exchange programmes need to be scaled up HIV testing is recommended nationwide in four countries and is prioritised in high prevalence areas or for key populations in the rest In 2015, PLHIV aware of their HIV status ranged from 26% to 89% Antiretroviral therapy (ART) is recommended for all PLHIV in Thailand and Maldives while six countries recommend ART at CD4 cell counts <500 cells/mm3 In 2015, 14 million (39%) PLHIV were receiving ART compared to 670,000 (20%) in 2010 Coverage of HIV testing and treatment among HIV-positive pregnant women has also improved but remains low in all countries except Thailand, which has eliminated mother-to-child transmission of HIV and syphilis Between 2010 and 2015, AIDS-related deaths and new HIV infections have shown a declining trend in all the high-burden countries except Indonesia But the region is far from achieving the 90-90-90 target by 2020 and the end of AIDS by 2030 The future HIV response requires that governments work in close collaboration with communities, address stigma and discrimination, and efficiently invest domestic resources in evidence-based HIV testing and treatment interventions for populations in locations that need them most